Clinical profile and therapeutic strategies in patients with arrhythmogenic cardiomyopathy treated in a national reference institute - Huerta Robles, Rocio (2021)
Objective. To determine the epidemiological, clinical, electrocardiographic, imaging characteristics and main therapeutic strategies performed in patients with arrhythmogenic cardiomyopathy treated in a national reference cardiovascular institute. Materials and methods. Observational, descriptive and retrospective study that attempts to identify the clinical characteristics, complementary tests and therapeutic strategies performed in patients with arrhythmogenic cardiomyopathy treated at the National Cardiovascular Institute - INCOR EsSalud in Lima, Peru. Results. Thirteen patients were found with arrhythmogenic cardiomyopathy. The median age at which the diagnosis was made was 38.2 years and 69.3% of those affected were male. The most frequent clinical manifestations were tachycardic palpitations (92.3%), presyncope (84.6%) and heart failure (69.2%). 23% of the patients suffered a cardiac arrest. All the patients presented at least one episode of ventricular tachycardia, 92.3% with complete left bundle branch block morphology and upper axis. 76.9% received an implantable cardioverter defibrillator (ICD), 15.3% underwent ablation and 15.3% received a heart transplant. 84.6% of the patients live to this day. Conclusions. Arrhythmogenic cardiomyopathy predominantly affected the young and male population. All the patients had a potentially fatal ventricular arrhythmia. Biventricular disease by echocardiography and cardiac magnetic resonance occurred in 69.2% and 100% of the cases, respectively. The therapeutic strategies used were antiarrhythmic medical treatment, placement of an ICD as secondary prevention, ablation, and heart transplantation. To date, 84.6% of patients survive.